The performance of dye removal by Malaysia seaweed biomass - Nur Nadiah, Razak (2016)
Textile industry generate millions of gallons of wastewater which consist of hazardous toxic waste, colours and chemical substances from dyeing process, finishing process and high pH and temperature. The textile wastewater gave negative effects towards environments such as the toxicity that causes death of aquatic organisms, sewage bacteria and plants. Adsorption process will be used as a physical method for the textile wastewater treatment. Therefore, the adsorption process will be done by using seaweed biomass with size that passed 0.7 – 1.5mm sieve to be the filter medium in order to treat the colour (dye). The data obtained from the adsorption of concentration of dye by using UV-vis spectrophotometer at 640 nm wavelength. All data will be represents the mean of triplicates with average and standard deviation. The experiments done by different types of seaweed to choose the best performance of dye removal.